1998
DOI: 10.1046/j.1365-3040.1998.00296.x
|View full text |Cite
|
Sign up to set email alerts
|

Elevated atmospheric [CO2] promotes frost damage in evergreen tree seedlings

Abstract: Growth under elevated [CO 2 ] promoted spring frost damage in field grown seedlings of snow gum (Eucalyptus pauciflora Sieb. ex Spreng.), one of the most frost tolerant of eucalypts. Freezing began in the leaf midvein, consistent with it being a major site of frost damage under field conditions. The average ice nucleation temperature was higher in leaves grown under elevated [CO 2 ] (-5·7°C versus -4·3°C), consistent with the greater incidence of frost damage in these leaves (34% versus 68% of leaves damaged).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
71
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(75 citation statements)
references
References 17 publications
(21 reference statements)
4
71
0
Order By: Relevance
“…Therefore, the slower recovery of F v /F m in plants grown at elevated p CO 2 is indicative of the imposition of an additional stress during the winter, which is not experienced by the control plants. Other evidence that overwintering leaves may be subjected to increased stress at elevated p CO 2 is provided by Lutze et al (1998) who showed increased frost damage to Eucalyptus pauciflora seedling leaves at elevated p CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, the slower recovery of F v /F m in plants grown at elevated p CO 2 is indicative of the imposition of an additional stress during the winter, which is not experienced by the control plants. Other evidence that overwintering leaves may be subjected to increased stress at elevated p CO 2 is provided by Lutze et al (1998) who showed increased frost damage to Eucalyptus pauciflora seedling leaves at elevated p CO 2 .…”
Section: Discussionmentioning
confidence: 99%
“…Experimental results suggest that responses are most likely species-specific, but there is a mounting consensus that, for many plant species, growth under elevated CO 2 can reduce their resistance and tolerance to freezing temperatures (Repo et al 1996, Lutze et al 1998, Barker et al 2005, Bertrand et al 2007). The reduction in tolerance appears to be caused by a slowdown in low-temperature acclimation (Loveys et al 2006), which is caused by higher daytime leaf temperatures due to reduced stomatal conductance under ; after the freeze setback, the canopy development resumed but did not achieve the normal level.…”
Section: Implications Of the 2007 Spring Freeze For A Changing Climatementioning
confidence: 99%
“…Similarly, the date of bud set in the autumn can either be advanced (Mousseau and Enoch, 1989;Murray et al, 1994) or delayed (Karnosky et al, in press). Both timing of bud break and bud set are important in determining frost and winter hardiness of northern trees species (Repo et al, 1996;Lutze et al, 1998;Wayne et al, 1998). Increased frost injury (Repo et al, 1996;Lutze et al, 1998) and increased winter dieback ) have both been described for trees growing under elevated atmospheric CO 2 in northern regions.…”
Section: Phenologymentioning
confidence: 99%
“…Both timing of bud break and bud set are important in determining frost and winter hardiness of northern trees species (Repo et al, 1996;Lutze et al, 1998;Wayne et al, 1998). Increased frost injury (Repo et al, 1996;Lutze et al, 1998) and increased winter dieback ) have both been described for trees growing under elevated atmospheric CO 2 in northern regions. Others have described a possible increased cold hardiness for some trees growing under elevated atmospheric CO 2 due to the buildup of soluble sugars that may act as cryoprotectants (Ö gren et al, 1997).…”
Section: Phenologymentioning
confidence: 99%